Isothermal and Two-Temperature Zone Selenization of Mo Layers. (23rd January 2012) - Kaupmees, L.; Altosaar, M.; Volobujeva, O.; Raadik, T.; Grossberg, M.; Danilson, M.; Mellikov, E.; Barvinschi, P.
Abstract : Glass/Mo, Mo foil, glass/Mo/In, and glass/Mo/Cu stacked layers were selenized in closed vacuum tubes by isothermal and/or two-temperature zone annealing in Se vapors. The selenization process was studied dependent on Se vapor pressure, temperature and time. Samples were selenized from 375 to 580 ° C for 30 and 60 minutes. The applied Se pressure was varied between 130 and 4 . 4 ⋅ 10 3  Pa. The increase of MoSe2 film thickness was found to depend on the origin of Mo. MoSe2 thickness d L on Mo-foil was much higher than on sputtered Mo layers, and it depended linearly on time and as a power function d L ~ P S e 1 / 2 on Se vapor pressure. The residual oxygen content in the formed MoSe2 layers was much lower in the two-zone selenization process. If Mo was covered with Cu or In before selenization, these were found to diffuse into formed MoSe2 layer. All the MoSe2 layers showed p -type conductivity.